Penentuan Goodwill Pendekatan Dua Kolom dengan Memperhitungkan Unsur Pajak Penghasilan pada Laporan Keuangan Kombinasi Bisnis - Karman, I Wayan; Khairiyah, Nurul Musfirah; Wijayani, Dahyang Ika Leni (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2024)
The assets and liabilities of the acquiree and the acquirer are combined because of the business merger. The value of goodwill will be recognized if there is a discrepancy between the entire investment value and the value of assets and liabilities recognized, or equity eliminated. Financial Accounting Standards No. 22 of 2014 solely considers the fair value of the net assets purchased for determining goodwill. The aim of this study is to define the amount of goodwill is determined using the two-column approach in PSAK 22 2014 when considering the income tax aspect of a business combination because, in accordance with the tax law, a business combination is an object of income tax. This study is qualitative descriptive that relies on doing literature reviews pertaining to the computation of goodwill. From the discussion's findings, it can be inferred that the acquirer would recognize more tax debt when assets and liabilities are combined, increasing goodwill. The calculation of goodwill when accounting for income tax components may be expressed algebraically: goodwill = consideration provided + prior ownership plus non-controlling interests plus taxes due minus net assets. Theoretically, the result is that the amount of goodwill recognized and recorded will increase in proportion to the amount of tax debt that is recognized when assets and liabilities are combined. The amount of tax that must be realized by the acquirer is implied managerially to be proportionate to the net assets that the acquirer has acquired.